THE SYNTHETIC GLYCAN KB295 OPTIMIZES MICROBIOME COMPOSITION AND FUNCTION IN ULCERATIVE COLITIS – RESULTS FROM A PROOF OF PRINCIPLE HUMAN STUDY. (22nd January 2022) - Meisner, Jeffrey; Bransford, Toni; Miller, Kelsey; Lee, Jackson; Jose, Adarsh; Giuggio, Michael; McComb, Megan; Humphries, Eric; Rosini, Madeline; Wingertzahn, Mark; Shanahan, Fergus; van Hylckama Vlieg, Johan E T; et al.
Abstract: The pathogenesis of ulcerative colitis (UC) involves genetic susceptibility, immune-mediated tissue injury and environmental factors including disturbances of the gut microbiota. Nearly all current approved therapies modify host immunity, rather than directly targeting the microbiota. Fecal microbiota transplantation provides encouraging evidence for the therapeutic potential of gut microbiome modulation. Bacteria in the GI tract are ecologically differentiated by their ability to use specific glycans as growth substrates, making glycans a promising and safe alternative to target the microbiome. To explore this, we used an ex vivo fecal microbiota culture system to identify a synthetic glycan (KB295) with desirable microbiological activity and conducted a proof of principle study of safety and tolerability of KB295 in patients with UC. Fecal microbial communities from healthy subjects were incubated anaerobically with and without (negative control) KB295. KB295 increased short chain fatty acid (SCFA) production across ten fecal samples to a median concentration of 47.0 mM compared to 15.2 mM with the negative control in culture supernatants, including increases in acetate, propionate, and butyrate in all cases. Metagenomic sequencing of the ex vivo fecal pellets revealed that KB295 depleted pathobionts in the family Enterobacteriaceae to a median relative abundance of 10.8% compared to 38.2% with the negative control. Pathobiont depletion was associated with enrichments of diverse genera in the phyla Bacteroidetes and Firmicutes . Twelve patients with mild to moderate UC were enrolled in an open-label single-arm study with an 8-week intake of KB295. KB295 was well tolerated with generally mild adverse events, and only one AE resulted in discontinuation. The most frequently occurring adverse events were changes in bowel habit, flatulence, and headache. Fecal calprotectin and lactoferrin decreased by median values of 69.0% (n=11) and 86.0% (n=6), respectively, from screening to the end of the KB295 intake. Consistent with the ex vivo preclinical findings, of the subjects for whom we have data to date, the relative abundance of the fecal pathobiont family Enterobacteriaceae decreased from five participants, and the commensal genus Parabacteroides was enriched in four of five participants. These results establish a proof of principle for the glycobiological modulation of gut microbiome composition and function and provide insight into the potential utility of this strategy in patients with ulcerative colitis. The safety, tolerability, and encouraging evidence for reduced inflammation with KB295 call for a Phase 2 study, which is planned.